Dynamics of water quality at different stocking densities and its effect on the growth of Vannamei shrimp (Litopenaeus vannamei) under intensive culture at PT Shihe Udang Industry Indonesia - Ainul Qadri; Ninis Trisyani; Nurul Rosana; Irma Faldila (Priviet Social Sciences Journal, 2026)
Vannamei shrimp (Litopenaeus vannamei) is a leading aquaculture commodity in Indonesia, with high market demand for both domestic consumption and export. However, cultivation continues to fail, primarily due to water quality problems. Water-quality parameters play a crucial role in the ecosystem of intensive shrimp ponds. This study aimed to determine the effect of stocking density on water quality and production outcomes. The research was conducted over one shrimp culture cycle at PT Shihe Udang Industry Indonesia. The results showed that the water-quality dynamics in all three observed ponds tended to increase as the day of culture progressed, and the parameters that most strongly influenced shrimp growth and production were NH4⁺, total organic matter, and total Vibrio count. The data indicate that higher stocking densities strongly affect water quality: Pond A1 (361 shrimp/m²) had more stable water quality than ponds A5 (637 shrimp/m²) and C (1,296 shrimp/m²). Production in Pond A1 was the most optimal at 11,220.31 kg, with a survival rate of 68% and a feed conversion ratio of 1.47. The lowest production occurred in Pond C at 1,484.56 kg, with a survival rate of 25% and a feed conversion ratio of 2.43. The poor production performance in Pond C was driven by the very high stocking density, which deteriorated water quality; the high total Vibrio count also contributed to shrimp mortality.